Patients' Length of Stay in Women Hospital and Its Associated Clinical and Non-Clinical Factors, Tehran, Iran - Ravangard, R (Kowsar, 2011)
BACKGROUND: Length of Stay (LOS) is an appropriate hospital indicator to evaluate hospital resource utilization rate, efficiency, and quality of services delivered. In this survey, we aimed to study hospital LOS and determine its association with clinical and non-clinical factors in Women Hospital in Tehran. METHODS: In this cross-sectional study, we reviewed all 3421 charts of patients admitted in Oncology, Surgery and Obstetrics units in 2008. We used a data collection sheet and conducted interviews to collect the following data: distance from living area, medical insurance coverage types, admission and discharge months, days and times, inpatient units, final diagnoses and the number of diagnostic tests. RESULTS: The overall median of the LOS in the studied hospital was 50.8 hours. The medians were 48.5, 54.4, and 94.2 hours in the Obstetrics, Surgical and Oncology units, respectively. Results showed that the associated factors with the LOS were patient admissions on Thursdays, admitting by residents, the number of performed diagnostic tests (p<0.001), suffering from neoplastic diseases (p=0.005) and spouse jobs. CONCLUSION: Among the associated factors, policy makers and managers can only change the admission days and the number of diagnostic tests to decrease the LOS. Further researches are needed to find other factors associated with LOS.